Influence of Anthropometric Dimensions on Pedals Activation Force and On H-Point Position - Ivan Grujic, Nadica Stojanovic, Nouby M. Ghazaly (International Journal of Advanced Science and Technology, 2019)
Besides the design, nowadays buyers are very demanding when comfort is taken into question; all commands must be reachable and adapted to their physics. During the development of new vehicles, manufacturers must take into the consideration many factors to be competitive on the market. The anthropometric dimensions of the driver are playing very important role in the vehicle development. So car manufacturers have tendency to make the vehicle that is convenient for wide people population. The acting force on the vehicle commands depends from the user physics; also the vehicle must have the possibility to increase this force as many times is necessary, to maintain safe vehicle control, as well as to not disturb the safety of other traffic participants. The analysis is conducted for wide American male population (1 – 99%), by the application of the RAMSIS software package. It is found that by increasing the anthropometric dimensions the clutch pedal acting force decreases while joint loads are growing. Besides that the H-point determination is conducted in respect to the foot commands while the comfort is not disturbed.Keywords: comfort, anthropometric, RAMSIS, force, loads.